Development and optimization of OspC chimeritope vaccinogens for Lyme disease. Issue 8 (18th February 2020) - Izac, Jerilyn R.; O'Bier, Nathaniel S.; Oliver, Lee D.; Camire, Andrew C.; Earnhart, Christopher G.; LeBlanc Rhodes, DeLacy V.; Young, Brandon F.; Parnham, Stuart R.; Davies, Christopher; Marconi, Richard T.
Highlights: Chv chimeritopes contain 18 linear epitopes from different OspC variants. Epitope ordering in OspC chimeritopes influences antibody responses. Inter-epitope linkers were not required for optimal antibody responses. Chv chimeritopes elicit broadly cross-reactive antibody. Immunization induced antibody has potent bactericidal activity. Abstract: Experimental Outer surface protein (Osp) C based subunit chimeritope vaccinogens for Lyme disease (LD) were assessed for immunogenicity, structure, ability to elicit antibody (Ab) responses to divergent OspC proteins, and bactericidal activity. Chimeritopes are chimeric epitope based proteins that consist of linear epitopes derived from multiple proteins or multiple variants of a protein. An inherent advantage to chimeritope vaccinogens is that they can be constructed to trigger broadly protective Ab responses. Three OspC chimeritope proteins were comparatively assessed: Chv1, Chv2 and Chv3. The Chv proteins possess the same set of 18 linear epitopes derived from 9 OspC type proteins but differ in the physical ordering of epitopes or by the presence or absence of linkers. All Chv proteins were immunogenic in mice and rats eliciting high titer Ab. Immunoblot and enzyme linked immunosorbent assays demonstrated that the Chv proteins elicit IgG that recognizes a diverse array of OspC type proteins. The panel included OspC proteins produced by N. American and European strains of the LD spirochetes. Rat anti-Chv antisera uniformly labeled intact, non-permeabilized Borreliella burgdorferi demonstrating that vaccinal Ab can bind to targets that are naturally presented on the spirochete cell surface. Vaccinal Ab also displayed potent complement dependent-Ab mediated killing activity. This study highlights the ability of OspC chimeritopes to serve as vaccinogens that trigger potentially broadly protective Ab responses. In addition to the current use of an OspC chimeritope in a canine LD vaccine, chimeritopes can serve as key components of human LD subunit vaccines.